2023
DOI: 10.1001/jamanetworkopen.2023.8437
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Survival Disparities Between Non-Hispanic Black and White Patients With Uterine Cancer

Abstract: ImportanceDisparities in survival exist between non-Hispanic Black (hereafter, Black) and non-Hispanic White (hereafter, White) patients with uterine cancer.ObjectiveTo investigate factors associated with racial disparities in survival between Black and White patients with uterine cancer.Design, Setting, and PatientsThis cohort study used data from the National Cancer Database on 274 838 Black and White patients who received a diagnosis of uterine cancer from January 1, 2004, to December 31, 2017, with follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…This can due to the mental, social, and financial support provided by their spouses [ 32 , 44 – 46 ]. Awareness of the symptoms and risk factors for this disease, and its early diagnosis, are usually coupled with higher levels of education and financial stability that enable women to lead a healthier lifestyle and have better access to preventive measures and quality of care [ 30 , 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can due to the mental, social, and financial support provided by their spouses [ 32 , 44 – 46 ]. Awareness of the symptoms and risk factors for this disease, and its early diagnosis, are usually coupled with higher levels of education and financial stability that enable women to lead a healthier lifestyle and have better access to preventive measures and quality of care [ 30 , 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the contribution of each factor set, we calculated the percentage of excess relative risk (hazard) of incident KFRT (and decreased relative risk of pre-KFRT death) in Black versus White veterans that was explained by that factor set. Excess relative risk was defined as HR minus 1.0, and decreased relative risk was defined as 1.0 minus HR, both denoted by D. We then calculated the explainable percentage using the formula (D base 2D base1factor )/ D base 3100%, 5,26,27 where D base and D base1factor are the values of D from the base model and each of the above models 2-8. In addition, we calculated the proportional reduction in the Wald chi-square statistic associated with the HR in each of the models 2-8 from the base model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Although adherence to quality standards provides potential strategies for intervention and mitigation by providers and health systems, several studies have shown that although quality treatment or other socioeconomic variables may improve survival, these factors alone do account for the persistent and growing disparities among minority women 93–96 . For example, in a large study using the National Cancer Database data of more than 270,000 Black and White women, survival disparity was noted (5-year survival, 58.6% vs. 78.5%) 96 . Estimated excess relative risk for survival was most attributable to histology in all women (~50%) and unexplained factors with slight differences in the proportional distribution by age (≤65 years old vs. older).…”
Section: Uterine Cancermentioning
confidence: 99%